2021
DOI: 10.1016/j.eclinm.2020.100700
|View full text |Cite
|
Sign up to set email alerts
|

Impact and acceptability of HIV self-testing for trans men and trans women: A mixed-methods subgroup analysis of the SELPHI randomised controlled trial and process evaluation in England and Wales

Abstract: Background: Globally, trans people are disproportionately affected by HIV, but research on strategies to increase testing are limited. SELPHI is a randomised-controlled-trial (RCT) of 10,135 cis men, trans men, and trans women reporting lifetime anal intercourse with male partners (cis or trans), evaluating whether the offer of free HIV self-testing (HIVST) increases diagnosis. This subgroup analysis from the SELPHI RCT aims to describe key HIVST outcomes and HIVST acceptability for trans people. Methods: SELP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…In this study, we found that web-based HIVST have reached many rst-time testers similar with previous studies among cis-MSM and TGW [25][26][27][28][29]. Reporting and linkage to care and prevention rates were high but ART and PrEP initiation were sub-optimal.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we found that web-based HIVST have reached many rst-time testers similar with previous studies among cis-MSM and TGW [25][26][27][28][29]. Reporting and linkage to care and prevention rates were high but ART and PrEP initiation were sub-optimal.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the inconsistencies, the anxiety regarding linkage to care and the desire for assistance have been reported among cis-MSM and TGW in the country [6], and other KP elsewhere [39]. Additionally, some transgender people have been documented to be needing some form of support during HIVST, mostly from social networks [29]. Secondly, while it may be intuitive that testing for the rst-time is associated with higher odds DAH, similar with previous studies [6, 23,40], it was the opposite in our bivariate model.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included studies had a quantitative descriptive design (n=28) [ 12 , 13 , 15 , 25 - 50 ]. In the remaining studies, a (quantitative) nonrandomized design was reported 6 times [ 32 , 51 - 55 ], a randomized controlled design was reported 5 times [ 56 - 60 ], a mixed methods design was reported 3 times [ 14 , 61 , 62 ], and a qualitative design was reported 3 times [ 63 - 65 ]. In 29 studies, a combination of services was offered; specifically, triage, testing, and a result service in 14 studies [ 13 , 28 , 40 , 42 , 46 , 49 , 51 - 53 , 56 , 57 , 59 , 60 , 63 ], triage and testing in 9 studies [ 26 , 27 , 29 - 33 , 35 , 37 ], and testing and a result service in 6 studies [ 41 , 44 , 45 , 48 , 61 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 29 studies, a combination of services was offered; specifically, triage, testing, and a result service in 14 studies [ 13 , 28 , 40 , 42 , 46 , 49 , 51 - 53 , 56 , 57 , 59 , 60 , 63 ], triage and testing in 9 studies [ 26 , 27 , 29 - 33 , 35 , 37 ], and testing and a result service in 6 studies [ 41 , 44 , 45 , 48 , 61 , 64 ]. Furthermore, 8 studies discussed a testing service [ 14 , 25 , 34 , 38 , 43 , 47 , 58 , 62 ], 7 discussed a result service [ 15 , 35 , 39 , 50 , 54 , 55 , 65 ], and 1 discussed a triage service [ 12 ]. In the included studies, the testing service was evaluated most often (ie, 82% of the studies).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation